Pertimbangan Hakim terhadap Pemalsuan Surat Keterangan Dokter: Studi Putusan Nomor 814/Pid.B/2020/PN SRG - Raynaldo Christoper Amanda Christoper (Jurnal Hukum Lex Generalis, 2026)
The forgery of health certificates during the COVID-19 pandemic is one of the criminal offenses that has had an impact on efforts to control the spread of the disease. This study aims to analyze the application of Article 263(1) of the Criminal Code, Article 268 of the Criminal Code, Article 14 of Law No. 4 of 1984 and Article 93 in conjunction with Article 9(1) of No. 6 of 2018 in Judgment No. 814/Pid.B/2021/PN SRG. The results of the study indicate that the defendant’s actions are more appropriately classified as the criminal offense of forging a medical certificate under Article 268 of the Criminal Code in conjunction with Article 55(1) of the Criminal Code.